2015
DOI: 10.1186/s13014-015-0529-y
|View full text |Cite
|
Sign up to set email alerts
|

CFAssay: statistical analysis of the colony formation assay

Abstract: BackgroundColony formation assay is the gold standard to determine cell reproductive death after treatment with ionizing radiation, applied for different cell lines or in combination with other treatment modalities. Associated linear-quadratic cell survival curves can be calculated with different methods. For easy code exchange and methodological standardisation among collaborating laboratories a software package CFAssay for R (R Core Team, R: A Language and Environment for Statistical Computing, 2014) was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 9 publications
0
46
0
1
Order By: Relevance
“…A standard colony formation assay was carried out to assess cell survival based on the ability of single cells to grow into colonies, as described previously with modication. 17 In brief, transfected cells (500 per well) were seeded in the 6-well plates in growth media. 14 days later, colonies were stained with 0.1% crystal violet and colonies containing more than 50 cells were counted.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…A standard colony formation assay was carried out to assess cell survival based on the ability of single cells to grow into colonies, as described previously with modication. 17 In brief, transfected cells (500 per well) were seeded in the 6-well plates in growth media. 14 days later, colonies were stained with 0.1% crystal violet and colonies containing more than 50 cells were counted.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…The systemic or granulosa-specific, but not oocyte-specific, ablation of HBP1 promotes follicle growth and oocyte production and is associated with reduced apoptotic signals in mouse granulosa cells (Dong et al, 2016). Moreover, in the hbp1- to grow into colonies, which is the gold standard for determining cell reproductive death after drug treatment (Braselmann, Michna, Heß, & Unger, 2015). In this study, L-HBP1 overexpression in Raji cells inhibited colony formation, indicating that L-HBP1 could affect cell cluster formation.…”
Section: Discussionmentioning
confidence: 63%
“…The results showed that the overexpression of L‐HBP1 inhibited cell proliferation and decreased cell counts of Raji cells. In vitro colony formation assays are based on the ability of single cells to grow into colonies, which is the gold standard for determining cell reproductive death after drug treatment (Braselmann, Michna, Heß, & Unger, ). In this study, L‐HBP1 overexpression in Raji cells inhibited colony formation, indicating that L‐HBP1 could affect cell cluster formation.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were repeated $3 times using independent samples. For colony assay, statistical analysis was performed using the CFAssay for R package (R Foundation for Statistical Computing, Vienna, Austria) (30). A 1-way ANOVA, followed by the Dunnett's test was used to detect significant differences between the means of $3 independent groups.…”
Section: Discussionmentioning
confidence: 99%